Comparing Online Webcam- and Laboratory-Based Eye-Tracking for the Assessment of Infants’ Audio-Visual Synchrony Perception - Bánki, Anna; de Eccher, Martina; Falschlehner, Lilith; Hoehl, Stefanie; Markova, Gabriela (Frontiers in Psychology, 2022)
Online data collection with infants raises special opportunities and challenges for developmental research. One of the most prevalent methods in infancy research is eye-tracking, which has been widely applied in laboratory settings to assess cognitive development. Technological advances now allow to conduct eye-tracking online with various populations, including infants. However, the accuracy and reliability of online infant eye-tracking remains to be comprehensively evaluated. No research to date has directly compared webcam-based and in-lab eye-tracking data from infants, similarly to data from adults. The present study provides a direct comparison of in-lab and webcam-based eye-tracking data from infants who completed an identical looking time paradigm in two different settings (in the laboratory or online at home). We assessed 4-6-month-old infants (n = 38) in an eye-tracking task that measured the detection of audio-visual asynchrony. Webcam-based and in-lab eye-tracking data were compared on eye-tracking and video data quality, infants’ viewing behaviour, and experimental effects. Results revealed no differences between the in-lab and online setting in the frequency of technical issues and participant attrition rates. Video data quality was comparable between settings in terms of completeness and brightness, despite lower frame rate and resolution online. Eye-tracking data quality was higher in the laboratory than online, except in case of relative sample loss. Gaze data quantity recorded by eye-tracking was significantly lower than by video in both settings. In valid trials, eye-tracking and video data captured infants' viewing behaviour uniformly, irrespective of setting. Despite the common challenges of infant eye-tracking across experimental settings, our results point towards the necessity to further improve the precision of online eye-tracking with infants. Taken together, online eye-tracking is a promising tool to assess infants’ gaze behaviour but requires careful data quality control. The demographic composition of both samples differed from the generic population on caregiver education: our samples comprised of caregivers with higher-than-average education levels, challenging the notion that online studies will per se reach more diverse populations.